The effects of combined conditioning strategies on aerobic endurance and coordination in early teens - KOVAÇI, Fatbardha; DERHEMI, Laureta; BAZE, Andi (Edelweiss Applied Science and Technology, 2025)
To examine the effects of combined aerobic endurance and coordination training on the physical fitness of early adolescents aged 10 to 12 years. A total of 226 participants were randomly assigned to an experimental group, which received integrated conditioning, and a control group that followed standard physical education routines. Fitness was evaluated using the 6-minute run (aerobic endurance), 30-meter sprint, Illinois agility test (coordination), as well as anthropometric measures like weight and BMI. The experimental group showed small to medium effect sizes in variables such as weight, BMI, heart rate, and agility, with the 6-minute run improving by an average of 28.79 meters. However, none of the differences were statistically significant (p > 0.05). Trends suggest potential practical benefits of combined training strategies. While results lack statistical significance, the observed trends indicate that integrated conditioning may positively impact physical fitness in early adolescents. This study contributes to the understanding of integrated conditioning strategies by providing preliminary evidence that combined aerobic and coordination training can positively influence physical fitness indicators in early adolescents. It highlights the potential practical benefits of such approaches, paving the way for further research to optimize teen fitness interventions and promote healthier development during this critical age.